EXPERIENTIAL LEARNING AS EDUCATION - Ryan, Thomas (International Journal of Learning and Instruction (IJLI), 2025)
Experiential learning (EL) is hands on authentic and practical learning. Learning by doing    experiences connects knowledge with skills required within the experience. EL involves steps and over time via critical reflection, refinement and learning empower learners as they enhance individual and collaborative skills. EL is linked to secondary and tertiary education within co-operative education, practicums, clinical placements, internships, work terms, field experience, simulation, and virtual reality. EL supports students as they move towards certain roles in a progressively multifaceted society.